Nocardia farcinica infection after facial lipolysis injection in an immunocompetent patient - Xu, Wei; Su, Fang; Ji, Youqi; Chen, Mengyuan; Hong, Xin; Zhuo, Bingqian; Ge, Yumei (The Journal of Infection in Developing Countries, 2026)
Introduction: Injection lipolysis is a widely used technique for the rapid reduction of localized fat deposits. Although complications such as non-tuberculous mycobacterial infections have been reported, Nocardia infections following this procedure remain rare. Case presentation: This report details a case of Nocardia infection in an immunocompetent patient after facial lipolytic agent administration. The patient exhibited amelioration of facial edema and resolution of chest rash following a course of amoxicillin-clavulanate treatment, ultimately achieving recovery and discharge. Conclusions: This case highlights the importance of considering Nocardia infection as a potential complication of lipolytic injections and provides valuable insights into its diagnosis and management.